Irbesartan attenuates renal injury with diabetic nephropathy rats - ZHANG Ya, HUANG Wen-hui, HOU Zhi-min, LIU Ju-xiang, LIU Jing (Jichu yixue yu linchuang, 2020)
Objective To observe the effect of Irbesartan on renal injury in diabetic nephropathy (DN) rats. Methods The rats were randomly divided into control group, DN model group and Irbesartan treatment group. At the age of 22 weeks, body weight, random blood sugar, serum creatinine,urea nitrogen,and 24-hour urinary microalbumin were measured.The morphological changes of kidneys were observed. The expression of microRNA-192 in rat kidney was detected by fluorescence quantitative PCR,the expression of TGF-beta 1, Zeb1 and collagen Ⅰ in rat kidney were detected by Western blot and immuno-histochemistry. Results Compared with the control group, the body weight, random blood sugar, serum creatinine,urea nitrogen,and 24-hour urinary micro-albumin of the model group rats increased significantly (P＜ 0.05); Compared with the DN group, the body weight, random blood sugar, serum creatinine,urea nitrogen,and 24-hour urinary micro-albumin of the Irbesartan treatment group rats decreased significantly(P＜0.05). Irbesartan treatment can improve the general condition and renal pathological damage of DN rats. Compared with the normal control group, the expression of microRNA-192 in the kidney of DN rats in the DN model group was down-regulated (P＜0.05), while that in the Irbesartan group was up-regulated (P＜0.05). WB and immuno-histochemical results showed that the expression of TGF-beta 1, ZEB1 and collagen Ⅰ protein in kidney tissue of DN model group was significantly increased as compared with that of normal group (P＜0.05); Compared with DN group, Irbesartan treatment reduced expression of TGF-beta 1, ZEB1 and collagen Ⅰ protein, with statistical significance (P＜ 0.05). Conclusions Irbesartan attenuates renal damage in diabetic nephropathy rats.